Investigating at the grassroots: exploring the origins, purposes journalistic practices and outcomes in two award-winning Daily Dispatch editorial projects - Lunga, Carolyne Mande (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2011)
This thesis explores the origins, purposes, journalistic practices and outcomes of two award-winning projects namely Broken Homes and Slumlords done by Daily Dispatch's Gcina Ntsaluba in 2009. The projects were described by the paper as investigative journalism but interestingly the original idea came from grassroots driven strategies and they were done by adopting alternative news gathering strategies and immersion in the ordinary people, inspired by public journalism. This thesis follows Christians et al's (2009) normative theoretical framework of press roles summarised as the monitorial, facilitative, collaborative and radical roles. It provides normative prescriptions of public and investigative journalism, development and radical journalism. It then draws on sociological theoretical critiques in order to provide an analytical overview of the complex matrix of political, economic and media contexts which influenced the origins, purposes, journalistic practices and outcomes of the two projects. Drawing on a critical realist case study design, the thesis goes on to provide a narrative account of the two projects based on the in-depth interviews exploring the editorial staffs ideas on the origins, purposes, journalistic practices and outcomes of the projects and a qualitative content/thematic analysis of the journalistic texts related to the projects. This primary data is then critically evaluated against normative theories of press performance, especially Nip's (2008) key practices and Haas's (2007) 'public philosophy' of public journalism. It is also evaluated against a normative framework of what constitutes "good investigative journalism" based on Ettema and Glasser (1998), Waisbord (2000) among others. Protess et al 1991's classic mobilisation model is used to interrogate the projects' outcomes. The thesis established that there was a close connection of the monitorial (investigative journalism), facilitative (public journalism) and radical (tabloid journalism) roles at the paper which shows that the roles are not mutually exclusive. The two projects however fell short of the collaborative role (development journalism) which can, partly, be attributed to the adversarial nature of the relationship between the state and the media. The Daily Dispatch also failed to activate a platform for deliberation and public problem solving. There might thus be more scope in adopting a 'facilitative monitorial role' which would not only expose those who violate other people's human rights, corrupt people and institutions that are not performing well. Instead it will also activate civic life and facilitate 'collaboration' between government and the publics in problem solving.
Keywords: Investigative reporting -- South Africa -- Eastern Cape; Citizen journalism -- South Africa -- Eastern Cape; Reporters and reporting -- South Africa -- Eastern Cape; Journalism -- Social aspects -- South Africa -- Eastern Cape; Journalism -- Political aspects -- South Africa -- Eastern Cape